Study on enhancing hydrogen production potential from renewable energy in multi-terminal DC system - Wei Deng (Elsevier, 2021)
Renewable energy complementary hydrogen production can enhance the full consumption of renewable energy and reduce the abandonment of wind and solar power. The integration of renewable energy and hydrogen production equipment through existing multi-terminal DC systems can reduce new power lines construction and save investment in distribution equipment. For integrated renewable energy/hydrogen energy in an existing multi-terminal DC system, this paper investigates its potential of hydrogen production based on renewable energy, while ensuring the normal performance of the existing system being not affected. The typical structure and control strategy of the integrated renewable energy/hydrogen energy in multi-terminal DC system are firstly described. Then the state space model of the system is constructed, and the key parameters affecting the hydrogen production capacity are studied by using the eigenvalues analysis method. Finally, the corresponding system simulation model and test platform are built, and the theoretical analysis results are verified, and the potential of using multi-terminal DC system to enhance hydrogen production is quantitatively analyzed. The proposed scheme can enhance the hydrogen production potential from renewable energy, meanwhile the normal performance of the existing system is not affected.